Hope for a Good Life Results of the Hope-Barometer International Research Program (Social Indicators Research Series,, 2018)
This volume addresses the convincing belief that hope is an existential need and resource for living a good life, not only when all is going well, but especially in difficult times. The findings reported in this volume result from the annual survey of the Hope-Barometer Research Program collected during 7 years and conducted in several countries. Structured in three parts, the first one provides the reader with a general introduction into the topic of hope, the theoretical and methodological foundations and major general results of the Hope-Barometer. Part two presents specific topics related to the levels and variations of hope across different population groups, and the relationship of hope with several measures of well-being. Further part three focuses on comparisons of elements and levels of hope across cultures discussing methods and techniques to improve hope and thus increase overall well-being.